Corrigendum to "System of coupled clamped beam equations: Existence and localization results" [Nonlinear Anal.: RWA 35 (2017) 45–60]. (February 2018) - Minhós, Feliz; Coxe, Infeliz
Abstract: Corrigendum to "System of coupled clamped beam equations: existence and localization results" [Nonlinear Anal.: RWA 35 (2017) 45–60].